Dietary-Induced Energy Expenditure: A Human Study - Bruce, Anne Morag (My University, 1985)
Indirect calorimetry was used to examine energy expenditure at rest and dietary-induced energy expenditure in normal-weight and overweight volunteers, whose daily energy intakes were similar. The influences of exercise, exercise training, and insulin on dietary-induced energy expenditure were also assessed. At rest energy expenditure was 70.3 kcals/hour in the overweight volunteers, 7.4 kcals/ hour greater than in the normal-weight volunteers. Consumption of a mixed meal of nearly 1000 kcals elicited similar increases in energy expenditure in the normal-weight and overweight volunteers of 10.8 kcals/hour and 12.5 kcals/hour respectively. The results refute the suggestion that a deficiency in energy expenditure at rest or in dietary-induced energy expenditure could be responsible for the greater propensity towards obesity in the overweight volunteers.
When exercise preceded the meal, the oxygen debt of exercise summated with the dietary-induced energy expenditure in the normal-weight group. The post-prandial response in the overweight group was similar whether or not exercise preceded the meal, even though the metabolic response to exercise alone was not impaired in the overweight group.
Six volunteers (four normal-weight and two over-weight) completed an exercise training programme, and increased their fitness level. However, dietary-induced energy expenditure in response to the 1000 kcal meal was similar before and after training.
Hyperinsulinaemia in six normal-weight, non-diabetic volunteers did not influence the post-prandial energy response, although the infusion of insulin and glucose itself elicited an obligatory increase in energy expenditure.
The work described in the thesis thus suggests that in mildly overweight individuals there is no evidence that reductions in post-prandial energy expenditure account for their excess weight, but that the lack of a further increase in post-prandial energy expenditure following exercise may do so. The results of the thesis indicate that exercise training does not alter post-prandial energy expenditure, and that hyperinsulinaemia does not influence post-prandial energy expenditure.
Keywords: Medical Sciences; Medical Sciences